KEKERABATAN Hoya (ASCLEPIADACEAE) SUMATERA BERDASARKAN KARAKTER MORFOLOGI - Rahayu, Sri (Center for Plant Conservation Bogor Botanic Garden, Indonesian Institute of Sciences, 2011)
Morphological relationships analysis of Hoya species from Sumatra was carried out. The study was taken both from the living collections at Bogor Botanic Garden and the herbarium specimens at Herbarium Bogoriense. There are 25 Hoya species in Sumatra resulted from the total of 129 samples number. Cluster analysis was run by Clique of Phylip software based on morphological diagnostic characters. Five paraphiletic groups were resulted from the phylogenic analyses. The groups constructed from this analysis were tending to be identical with the Schlecters section classification.